Title Governmental energy Efficiency certifications in buildings: A comparative analysis of EPC (EU), PBE Edifica (BR), Energy Star (USA), and ESGB (CHN) - Bessa, Erik Silvie Dias; Muniz, Pablo Rodrigues; Bertulani, Lucas Duarte (Latin American Journal of Energy Research, 2025)
Globally, buildings account for a significant share of energy consumption and greenhouse gas emissions, which has driven the creation of certification models to assess their energy performance. This study compares four governmental certifications: the Energy Performance Certificate (EPC) in the European Union, the Brazilian Building Energy Labeling Program (PBE Edifica), Energy Star in the United States, and the Evaluation Standard for Green Building (ESGB) in China. Based on documentary and bibliographic research, the analysis considered institutional origin, scope, methodologies, criteria, rating scales, certification processes, mandatory requirements, costs, and impacts. The study concludes that the effectiveness of these instruments depends on technical rigor, consistent public policies, and fiscal incentives, making them strategic tools for energy transition and urban sustainability.